Effects of a family interdisciplinary intervention on food processing and the stage of eating behavior change in overweight or obese adolescents.: INTERVENÇÃO INTERDISCIPLINAR FAMILIAR NO PROCESSAMENTO DE ALIMENTOS E A FASE DA MUDANÇA DE COMPORTAMENTO ALIMENTAR - Ribeiro Geraldi, Ana Paula; Marques, Déborah; Sanabria Miranda, Clara Camille; Vicentini de Oliveira, Daniel; Rodrigues Lourenço de Morais, Samuel; Badilla, Pablo Valdés; Zanqueta Carvalho, Isabelle; Magnani Branco, Braulio Henrique (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Due to the increasing prevalence of obesity in recent years, the treatment of excess weight has become necessary and a global public health problem, especially in childhood and adolescence. Objective: The present study aimed to analyze the effects of an interdisciplinary intervention on the processing and food consumption behavior of overweight and obese adolescents. Methods: This is a pre-experimental, analytical, and interventional study. Sixty-four adolescents (65% females and 35% males), with a mean age of 13.72 ± 2.46 years, who were overweight or obese, were included in the study. The interdisciplinary interventions took place over 12 weeks, three times a week, with the participation of an interdisciplinary team composed of physical education professionals (three times a week), nutritionists (twice a week), and psychologists (twice a week). To analyze the level of food processing, a 3-day food record was applied before and after the 12 weeks of intervention. Foods were calculated in grams, calories, and % of total energy value (TEI). Data were expressed as mean and standard deviation. Subsequently, the normality of the data was tested using the Kolmogorov-Smirnov test. After this confirmation, a paired t-test was performed to compare the pre-and post-intervention moments. Results: significant reduction in processed and ultra-processed foods and increased consumption of fresh foods in grams and calories (p<0.05). However, no significant differences were observed for consuming minimally processed foods (p>0.05). In addition, there were significant results in the domain portion size and quantity (p<0.01) and consumption of fruits and vegetables (p<0.05). Conclusion: 12 weeks of interdisciplinary interventions provided positive impacts on the level of food processing and consumption behavior of overweight and obese adolescents, contributing to the fight against obesity in adolescence.